Humoral Hypercalcemia of Malignancy with a Parathyroid Hormone-Related Peptide-Secreting Intrahepatic Cholangiocarcinoma Accompanied by a Gastric Cancer - Katsushi Takeda; Ryosuke Kimura; Nobuhiro Nishigaki; Shinya Sato; Asami Okamoto; Kumiko Watanabe; Sachie Yasui (Case Reports in Endocrinology)
Humoral hypercalcemia of malignancy (HHM) is caused by the oversecretion of parathyroid hormone-related peptide (PTHrP) from malignant tumors. Although any tumor may cause HHM, that induced by intrahepatic cholangiocarcinoma (ICC) or gastric cancer (GC) is rare. We report here a 74-year-old male who displayed HHM with both ICC and GC and showed an elevated serum PTHrP level. Treatment of the hypercalcemia with saline, furosemide, elcatonin, and zoledronic acid corrected his serum calcium level and improved symptoms. Because treatment of ICC should precede that of GC, we chose chemotherapy with cisplatin (CDDP) and gemcitabine (GEM). Chemotherapy reduced the size of the ICC and decreased the serum PTHrP level. One year after diagnosis, the patient was alive in the face of a poor prognosis for an ICC that produced PTHrP. Immunohistochemical staining for PTHrP was positive for the ICC and negative for the GC, leading us to believe that the cause of the HHM was a PTHrP-secreting ICC. In conclusion, immunohistochemical staining for PTHrP may be useful in discovering the cause of HHM in the case of two cancers accompanied by an elevated serum PHTrP level. Chemotherapy with CDDP and GEM may be the most appropriate treatment for a PTHrP-secreting ICC.